2024
DOI: 10.3389/fendo.2023.1325454
|View full text |Cite
|
Sign up to set email alerts
|

Association between the weight-adjusted waist index and the odds of type 2 diabetes mellitus in United States adults: a cross-sectional study

Dongdong Zheng,
Suzhen Zhao,
Dan Luo
et al.

Abstract: ObjectiveTo examine the association between the weight-adjusted waist index (WWI) and the odds of type 2 diabetes mellitus(T2DM)among U.S. adults.MethodsData from the National Health and Nutrition Examination Survey (NHANES) spanning six years (2007–2018) were utilized, encompassing 31001 eligible participants. Weighted multivariate logistic regression models and smoothed fit curves were employed to assess the association between WWI and the odds of T2DM, as well as dose-response relationships in the overall p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…This nding highlights the potential application value of WWI as a novel indicator in diabetes prevalence assessment. Although a study by Sun et al [15] in the Japanese population indicated that WWI did not show superior predictive power compared to traditional indicators, this does not diminish its potential as a promising alternative or complementary tool for further evaluation in different populations.…”
Section: Discussionmentioning
confidence: 90%
“…This nding highlights the potential application value of WWI as a novel indicator in diabetes prevalence assessment. Although a study by Sun et al [15] in the Japanese population indicated that WWI did not show superior predictive power compared to traditional indicators, this does not diminish its potential as a promising alternative or complementary tool for further evaluation in different populations.…”
Section: Discussionmentioning
confidence: 90%